Self-monitoring and treatment of chronic non-communicable diseases in the context of the COVID-19 pandemic. Consensus of experts of the National society of evidence-based pharmacotherapy and the Russian society of the prevention of non-communicable diseases - S. Yu. Martsevich; N. P. Kutishenko; Yu. V. Lukina; S. N. Tolpygina; L. P. Ivanova; N. A. Dmitrieva; A. V. Kontsevaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
In the current epidemic of a new coronavirus infection, COVID-19 treatment of patients with chronic non-communicable diseases (NCDS) and cardiovascular diseases (CVD), in particular, requires close attention of doctors. The main objectives of such patients’ management tactics are to ensure that patients comply with self-isolation measures that prevent infection, motivate patients to follow all medical recommendations. Special attention should be paid to comply with recommended treatment of CVD. In the case of an infectious disease, it is necessary to assess the prescribed therapy for interaction with medications already taken by the patient. However, the tactics for COVID-19 therapy, including in patients with NCDS, may change over time, since there are currently no drugs with proven effectiveness for the treatment of a new coronavirus infection.